MEMBANGUN MASYARAKAT MADANI MELALUI HARMONI NILAI ISLAM DAN BUDAYA DI MOMENTUM MILANGKALA PWS SUMUT: Masyarakat Madani - Neng Nurcahyati Sinulingga; Dadan Ramdan; Amsal Qori Dalimunthe (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2025)
Rapid and complex social changes have triggered challenges in society, such as the weakening of local cultural identity, the strengthening of narrow religious views, and the emergence of a generation gap. In response to these issues, the Community Service activity titled “Building a Civilized Society through the Harmony of Islamic and Cultural Values at the 89th Anniversary of PWS Sumut” was conducted with the aim of reinforcing the social, spiritual, and cultural bonds of the Sundanese community in North Sumatra. The activity employed a service-learning approach with a participatory methodology, involving religious leaders, traditional figures, youth, and the general public in various activities such as intergenerational discussions, cultural and Islamic literacy training, Islamic-Sundanese art performances, and workshops on strengthening cultural identity. The results of the activity show that the integration of moderate Islamic values with local culture can be an effective strategy in forming an inclusive, dignified, and civilized society. The PWS Sumut Milangkala Momentum not only succeeded in strengthening the collective identity of the community but also became a social education space that revived the spirit of tolerance, mutual cooperation, and appreciation for diversity as a social strength.